Crescent dawn [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Dirk Pitt adventure., 2010)
In A.D. 327, a Roman galley barely escapes a pirate attack with its extraordinary cargo. In 1916, a British warship explodes in the middle of the North Sea. In the present day, a cluster of important mosques in Turkey and Egypt are wracked by explosions. Does anything tie them together? NUMA director Dirk Pitt is about to find out, as Roman artifacts discovered in Turkey and Israel unnervingly connect to the rise of a fundamentalist movement to restore the Ottoman Empire.